Vitamin B12 supplementation influences methylation of genes associated with Type 2 diabetes and its intermediate traits. (January 2018) - Yadav, Dilip K; Shrestha, Smeeta; Lillycrop, Karen A; Joglekar, Charu V; Pan, Hong; Holbrook, Joanna D; Fall, Caroline HD; Yajnik, Chittaranjan S; Chandak, Giriraj R
Aim: To investigate the effect of B12 and/or folic acid supplementation on genome-wide DNA methylation.Methods: We performed Infinium HumanMethylation450 BeadChip (Zymo Research, CA, USA) assay in children supplemented with B12 and/or folic acid (n = 12 in each group) and investigated the functional mechanism of selected differentially methylated loci.Results: We noted significant methylation changes postsupplementation in B12 (589 differentially methylated CpGs and 2892 regions) and B12 + folic acid (169 differentially methylated CpGs and 3241 regions) groups. Type 2 diabetes-associated genes TCF7L2 and FTO; and a miRNA, miR21 were further investigated in another B12 -supplementation cohort. We also demonstrate that methylation influences miR21 expression and FTO, TCF7L2, CREBBP/CBP and SIRT1 are direct targets of miR21-3p .Conclusion: B12 supplementation influences regulation of several metabolically important Type 2 diabetes-associated genes through methylation of miR21 . Hence, our study provides novel epigenetic explanation for the association between disordered one carbon metabolism and risk of adiposity, insulin resistance and diabetes and has translational potential.